Emotions in motion: impact of emotion understanding on children's peer action coordination. Issue 4 (18th May 2020) - Viana, Karine M. P.; Zambrana, Imac Maria; Karevold, Evalill Bølstad; Pons, Francisco
ABSTRACT: Peer action coordination has been often studied in terms of its underlying cognitive mechanisms, and little is known about its emotional processes. The aim of the present study was to investigate the extent to which children's emotion understanding explains their coordination of actions with a peer in a cooperative sensorimotor problem-solving task. Sixty-eight 5- to 9-year-old children were assessed for their emotion understanding with the Test of Emotion Comprehension (TEC) and for their problem-solving capacities with a sensorimotor task in an individual setting (individual sensorimotor skills) and in a cooperative setting (peer action coordination). The results showed that higher levels of emotion understanding significantly explained greater peer action coordination, even when controlling for age, gender and the child's individual sensorimotor skills. The findings point to the existence of emotional mechanisms – more specifically the role of emotion understanding – underlying successful coordination of actions in peer interaction. Theoretical and educational implications of having emotion understanding abilities for coordinating actions with others are discussed.